It takes a village: Influencing policy and practice to prevent alcohol use in pregnancy and promote better outcomes for individuals living with Fetal Alcohol Spectrum Disorder - Finlay-Jones, Amy; Elliott, Elizabeth; Chapman, Astrid; Halliday, Jane; Jones, Heather; Kippin, Natalie; Mullan, Narelle; Passmore, Hayley; Reibel, Tracy; Reynolds, Neil; Symons, Martyn; Tsang, Tracey; et al. (International Journal of Population Data Science, 2022)
Fetal Alcohol Spectrum Disorder (FASD) is a neurodevelopmental disorder caused by exposure to alcohol in utero. It has pervasive, lifelong impacts and is recognised as a major public health concern in many countries where alcohol is used. The FASD Research Australia Centre of Research Excellence (CRE) was funded by the National Health and Medical Research Council to generate and translate evidence to address prevention, diagnosis, and management of FASD in Australia. The current paper describes the approach to policy and practice impact taken by our CRE, including our stakeholder engagement processes and the key principles that underlie our approach. We provide examples of policy and practice influence in FASD prevention, diagnosis and management that have been achieved over the past five years and discuss challenges that are routinely faced in the translation of our work.